BENTUK DAN MAKNA VARIASI BAHASA DALAM CERITA PENDEK BERBASIS KEARIFAN LOKAL - Nurfiana, Nina; Uswati, Tati Sri; Nuryanto, Tato (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2019)
(Title: Form and Meaning of Language Variation in Short Stories Based on Local Wisdom). The purpose of this studyis to analyze the form and meaning of language variations in short stories based on the local wisdom of XI MIA 3 students at SMAN 1 Astanajapura. The method that used in this research is descriptive qualitative. Based on the data and results of the analysis, it can be concluded that the variety of languages used in short stories which based on local wisdomis diverse. In the short stories there are alsolanguage variations in the terms of speakers that related to dialect and sociolec. The benefits ofthis studyin education can be used for learning Indonesian and literature, such as KD Indonesian specialization in class XII, that is 3.5 to identify sentences in various languages, so that it is used as a reference in identifying various languages. Meanwhile, it can be used as reference materials for other researchers, especially in sociolinguistic. Keywords: language variations, forms, meanings, short stories, local wisdom